Dynamics of the Sphere Model of Consciousness: Silence, Space, and Self - Pintimalli, Andrea; Di Giuseppe, Tania; Serantoni, Grazia; Glicksohn, Joseph; Ben-Soussan, Tal D. (Frontiers in Psychology, 2020)
The Sphere Model of Consciousness (SMC) delineates a sphere-shaped matrix that aims to describe subjective experiences using geometric coordinates, in accordance with a neurophenomenological perspective. According to the SMC, an experience of overcoming the habitual self and the conditioning of memories could be placed at the center of the matrix, which can then be called the Place of Pre-Existence (PPE). The PPE is causally associated with self-determination. In this context, we suggest that silence could be considered an intentional inner environment enabling self-perception to focus on the “here and now,” which in turn improves perception of one’s own body in space. To investigate the hypotheses grounded in the model, the current preliminary study examined the Place of Pre-Existence Technique (PPEt), in which practitioners are guided to focus on a self-defined aim, reach a state of detachment from the habitual self, and envision the future. Four-hundred eighty-one volunteer PPEt practitioners completed self-report questionnaires before and after an intensive 3-day meditative training. We analyzed potential relationships between subjective experiences related to physical, emotional, mental, temporal, and spatial components, as well as self-determination and silence, before and after training. The results indicated a transition from a prevailing influence of mental dimension on the other aspects of experience, to a prevailing influence of the spatial dimension. Silence was reported more often following the training and was predominantly related to mental and emotional experiences. The results are discussed in the framework of the SMC, as compared to other models, and in relation to the shift from Narrative to Minimal Self and to increased balance among the considered dimensions.